Automated variable aortic control versus complete aortic occlusion in a swine model of hemorrhage. Issue 4 (April 2017) - Williams, Timothy K.; Neff, Lucas P.; Johnson, Michael Austin; Russo, Rachel M.; Ferencz, Sarah-Ashley; Davidson, Anders J.; Clement, Nathan F.; Grayson, John Kevin; Rasmussen, Todd E.
Abstract : BACKGROUND: Future endovascular hemorrhage control devices will require features that mitigate the adverse effects of vessel occlusion. Permissive regional hypoperfusion (PRH) with variable aortic control (VAC) is a novel strategy to minimize hemorrhage and reduce the ischemic burden of complete aortic occlusion (AO). The objective of this study was to compare PRH with VAC to AO in a lethal model of hemorrhage. METHODS: Twenty-five swine underwent cannulation of the supraceliac aorta, with diversion of aortic flow through an automated extracorporeal circuit. After creation of uncontrolled liver hemorrhage, animals were randomized to 90 minutes of treatment: Control (full, unregulated flow; n = 5), AO (no flow; n = 10), and PRH with VAC (dynamic distal flow initiated after 20 minutes of AO; n = 10). In the PRH group, distal flow rates were regulated between 100 and 300 mL/min based on a desired, preset range of proximal mean arterial pressure (MAP). At 90 minutes, damage control surgery, resuscitation, and restoration of full flow ensued. Critical care continued for 4.5 hours or until death. Hemodynamic parameters and markers of ischemia were recorded. RESULTS: Study survival was 0%, 50%, and 90% for control, AO, and VAC, respectively ( p < 0.01). During intervention, VAC resulted in more physiologic proximal MAP (84 ± 18 mm Hg vs. 105 ± 9 mm Hg, p < 0.01) and higher renal blood flow than AO animals ( p = 0.02). During critical care, VAC resulted in higher proximal MAP (73 ± 8 mm Hg vs. 50 ± 6 mm Hg, p < 0.01), carotid and renal blood flow ( p < 0.01), lactate clearance ( p < 0.01), and urine output ( p < 0.01) than AO despite requiring half the volume of crystalloids to maintain proximal MAP ≥50 mm Hg ( p < 0.01). CONCLUSION: Permissive regional hypoperfusion with variable aortic control minimizes the adverse effects of distal ischemia, optimizes proximal pressure to the brain and heart, and prevents exsanguination in this model of lethal hemorrhage. These findings provide foundational knowledge for the continued development of this novel paradigm and inform next-generation endovascular designs. Abstract : Supplemental digital content is available in the text.